MEDIA KONVENSIONAL & SOSIALISASI PEMERINTAH DESA - Yudha Asmara Dwi Aksa (Fakultas Komunikasi, Sastra, dan Bahasa, 2018)
Media and local government are important research objects to provide information, understanding and education to the community. The present research analyses stages of dissemination to the public Sukaraja Village based on three models of Effendy (1997): one-step flow of communication, two-step flow of communication that explains the process of mass communication as well as SMCR model of Berlo that explains the communication process in general. To obtain data, the present research conducted observation, interviews, and literature review by compiling the existing resources materials and analyzing them based on the main theories above. The results indicated that an outline of community outreach programs performed by Sukaraja village can be categorized into two types: routine and non-routine outreach programs in various fields such as health, safety, and social development. Local government of Sukaraja Village used conventional media to deliver messages of the community’s character, culture and education. Furthermore, it shows the public acceptance community outreach programs of the government of Sukaraja village. The present research indicated the benefits of using conventional media such as billboard or radiogram in lieu of non conventional media such as email. Thus, the use of conventional media can be beneficial depending on the conditions of said society.